2020
DOI: 10.1074/jbc.ra120.013444
|View full text |Cite
|
Sign up to set email alerts
|

α2,3 linkage of sialic acid to a GPI anchor and an unpredicted GPI attachment site in human prion protein

Abstract: Prion diseases are transmissible, lethal neurodegenerative disorders caused by accumulation of the aggregated scrapie form of the prion protein (PrPSc) after conversion of the cellular prion protein (PrPC). The glycosylphosphatidylinositol (GPI) anchor of PrPC is involved in prion disease pathogenesis, and especially sialic acid in a GPI side chain reportedly affects PrPC conversion. Thus, it is important to define the location and structure of the GPI anchor in human PrPC. Moreover, the sialic acid linkage ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…1D). Consistent with this, GPI-APs purified from brain, kidney, and skeletal muscle were reported to be modified with the GalNAc side chain (5)(6)(7)51,52). The tissue-specific expression of PGAP4 suggests that the GPI-GalNAc side chain regulates certain specific but non-essential functions of GPI.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 53%
See 1 more Smart Citation
“…1D). Consistent with this, GPI-APs purified from brain, kidney, and skeletal muscle were reported to be modified with the GalNAc side chain (5)(6)(7)51,52). The tissue-specific expression of PGAP4 suggests that the GPI-GalNAc side chain regulates certain specific but non-essential functions of GPI.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 53%
“…Therefore, combined with a previous report (40), it is suggested that asialo forms of GPI-GalNAc side chain (Gal-GalNAc-GPI and GalNAc-GPI) has protective function from prion diseases. Because human PrP C GPI is more likely to be sialylated (approximately 40% in human brain (7)) than mouse PrP C GPI, augmented desialylation on the GPI-GalNAc side chain may be an effective novel therapeutic for treating human prion diseases. Elucidation of the relationship between structure and function of the GPI-GalNAc side chain will facilitate our understanding of the pathology of prion diseases and the development of therapeutics based on the structure of the GPI-GalNAc side chain.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…In mammalian brain, galactosylated and sialylated GPI-anchors are more abundant than in other tissues. However, not all GPI-anchored proteins are modified to the same extent with some proteins having only GalNAc instead of additional galactose and sialic acid modifications ( Kobayashi et al, 2020 ). Sialylation of the human prion protein side chain may contribute to the pathology of prion disease ( Bate et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The Golgi-resident galactosyltransferase B3GALT4 catalyzes the transfer of a galactose from UDP-galactose to the side chain GalNAc residue ( Wang et al, 2020 ). The GPI sialyltransferase was not identified yet, but recently it was found that in prion protein the sialic acid N-acetylneuraminic acid (Neu5Ac) is present in α2,3-linkage ( Kobayashi et al, 2020 ).…”
Section: Gpi-anchor Glycan Biosynthesis In Mammals and Yeastmentioning
confidence: 99%
“…They both harbor a glycosylphosphatidylinositol anchor (GPI anchor) and can be released from the cell membrane by the action of phospholipases. Interestingly, the GPI anchor, consisting of a phospholipid tail, a glycan core and a phosphoetanolamine linker to which the protein is attached, contains a glycolipid that can be sialylated as well (100)(101)(102). Therefore, CD24 and CD52 are glycoproteins attached to a glycolipid, which makes their context highly interesting for future studies.…”
Section: Influence Of Protein/lipid Context On Siglec Bindingmentioning
confidence: 99%